PEMANFAATAN JERAMI PADI DALAM PEMBUATAN KOMPOS PADA KELOMPOK WANITA TANI DI DESA UJUNG KARANG KECAMATAN KARANG TINGGI KABUPATEN BENGKULU TENGAH - Serawai, Bembi Akbar; Fitri, Melani Anisa (Jurnal Abdi Insani, 2024)
Central Bengkulu Regency has the potential to increase rice production, this condition is reflected increase in the area of ​​rice harvest by 168 hectares in the period 2022-2023. The potential not only contributes to increasing rice production but also the straw waste produced by the commodity. So far, people are accustomed to piling up straw waste from the harvest and burning it. This condition causes bad air pollution after harvest, waste from straw piles can also become a nest for some plant pests and diseases which can ultimately attack the farming business being run. This Community Service aims to increase the knowledge of women's farmer group members regarding the use of straw as compost. The stages in this Community empowerment include a survey of the activity location, implementation of activities and evaluation. Based on the results of the implementation and evaluation of activities, there was an increase in knowledge of 5% in terms of general knowledge of compost, in terms of knowledge regarding the purpose of using compost there was an increase of 11%. The knowledge of KWT members increased in the aspect of the influence of the use of compost fertilizer by 22%, while knowledge about the benefits of rice straw as the main ingredient for making compost increased by 17%. In the aspect of compost making techniques, there was a significant change in knowledge, before the counseling was carried out, 56% of KWT members did not know the technique of making compost from rice straw, after being given counseling, knowledge changed to Knowing Enough by 50% and Knowing by 44%. Based on these results, empowerment activities were successful in providing additional knowledge related to making compost from rice straw. Keywords: Agricultural Waste, Rice Straw, Compost, Community Service